3D micro/nano hydrogel structures fabricated by two-photon polymerization for biomedical applications - Fu, Hongxun; Yu, Baojun (Frontiers in Bioengineering and Biotechnology, 2024)
Hydrogels are three-dimensional natural or synthetic cross-linked networks composed of polymer chains formed by hydrophilic monomers. Due to the ability to simulate many properties of natural extracellular matrix, hydrogels have been widely used in the biomedical field. Hydrogels can be obtained through a variety of polymerization strategies such as heating and redox. However, photochemistry is one of the most interesting methods for researchers in this field. Gelatinmethacryloyl (GelMA) inherits the biological activity of gelatin and has become one of the gold standards in the field of biomaterials. GelMA, as a photopolymerizable hydrogel precursor, can be used to fabricate 3D porous structures for biomedical applications through two-photon polymerization.We report a new formulation of GelMA-based photoresist and used it to manufacture a series of twophoton polymerization structures, with a maximum resolution less than 120nm. The influence of process parameters on 3D structures manufacturing is studied by adjusting the scanning speed, laser power, and layer spacing values in two-photon polymerization processing. In vitro biological tests show that the 3D hydrogel produced by two-photon polymerization in this paper is biocompatible and suitable for MC3T3-E1 cell.